Low-viscosity high-hardness ultraviolet curing polyurethane resin and preparation method thereof

By using a polyester acrylate structure synthesized by low molecular weight hydroxy acrylate and diisocyanate, the problems of high viscosity and low hardness of traditional polyurethane resin are solved, and the ultraviolet cured polyurethane resin with low viscosity and high hardness are achieved, which is suitable for power battery insulation. sexual ink.

CN119432304APending Publication Date: 2025-02-14DONGGUAN CLIMAX SEAL TECH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411549135.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-01
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

The polyurethane resin in traditional photocuring inks has high viscosity and is difficult to meet the long-term safety performance requirements. The spray quality is unstable, making it difficult to meet the increasingly stringent market requirements.

Method used

The polyester acrylate structure formed by low molecular weight hydroxy acrylate and diisocyanate under the action of a catalyst is used to synthesize a low viscosity and high hardness ultraviolet cured polyurethane resin with a low viscosity and high hardness.

Benefits of technology

It realizes the low viscosity and high hardness of polyurethane resin, has good insulation performance, water resistance and humidity resistance, and is suitable for power battery insulating inkjet printing process.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The invention discloses a low-viscosity high-hardness ultraviolet curing polyurethane resin which comprises the following components in parts by weight: 30-45 parts of acrylic hydroxyl ester; 20 to 30 parts of diisocyanate; 0.1 to 0.2 part of a catalyst; 1-3 parts of a polymerization inhibitor; 25 to 35 parts of a diluent; 1-3 parts of an antioxidant; and 1-5 parts of a photoinitiator. The invention further discloses a preparation method of the low-viscosity and high-hardness ultraviolet curing polyurethane resin. The viscosity and the hardness of the ultraviolet curing polyurethane resin are doubly optimized; on the basis of having considerable insulativity, low viscosity and high hardness are ensured, so that the requirements for preparing the insulating ink are met. Moreover, the comprehensive performance of the ink is greatly improved, so that the ink has excellent performance in the aspects of viscosity, hardness, insulativity, boiling resistance and the like, and is suitable for the application scene of a power battery insulativity ink jet printing process.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to an ultraviolet light-cured polyurethane resin, in particular to a low-viscosity and high-hardness ultraviolet light-cured polyurethane resin and a preparation method thereof. Background Art

[0002] With the continuous advancement of science and technology in contemporary society, the development speed of industries such as consumer electronics and new energy vehicles is accelerating. On the basis of improving the ultimate performance, attention has been paid to high efficiency, environmental protection, energy conservation and emission reduction to meet the needs of consumer electronics, new energy vehicles and other fields. Among them, the packaging and integration of power batteries are crucial links. On the premise of meeting their industrial production, they are required to have high production efficiency, excellent yield, low cost, safety and reliability, and good promotion value of volume utilization. The excellent hardness protection in the outer packaging of power batteries can improve the safety and reliability of the battery, reduce the hidden dangers of leakage caused by external damage such as friction and scratches, and at the same time improve the volume utilization, leaving room for subsequent battery integration upgrades, and help designers achieve the goal of lightweight batteries.

[0003] The outer layer of the battery cell packaging protection is mainly divided into PET blue film wrapping and photocurable ink printing. The former is limited by the glue performance and construction process, and it is difficult to achieve complete bonding, while the latter perfectly solves this problem and can provide more comprehensive protection for the battery. However, since the polyurethane resin used in traditional photocurable inks is mainly a polymer material, its viscosity is high, resulting in unstable spraying quality, and the hardness is difficult to meet the requirements of long-term safety performance. The risk of failure is high and it is difficult to meet the increasingly stringent market requirements. Therefore, how to obtain a photocurable polyurethane resin with excellent properties such as high hardness, low viscosity, and moisture and heat resistance has become a problem that needs to be solved urgently.

[0004] In order to improve the hardness of light-cured polyurethane resin, the related patent CN201711064341.5 "A POSS-modified high-hardness polyurethane odorless wood paint" uses cage-type polysilsesquioxane-modified isocyanate trimer to form a curing agent containing 16 isocyanates, which is then used to synthesize a polyurethane resin with high hardness. Patent CN202311480240.1 "A method for preparing a high-hardness, friction-resistant hardening coating" uses aliphatic polyurethane acrylate and multifunctional acrylate monomers compounded with silica or aluminum oxide, and combines the properties of acrylate, polyurethane, and silica to prepare a light-cured polyurethane resin material with high hardness.

[0005] The manufacture of polyurethanes typically involves a multi-step chemical reaction, the most critical of which is the reaction of isocyanate groups (-NCO) with hydroxyl groups (-OH) to form carbamate groups (-NH-CO-O-).

[0006] Traditional one-component polyurethane is a polymer material made by the reaction of isocyanate and polyol, with molecular weights ranging from thousands to millions of Daltons. The molecular weight of linear polyurethane is usually between 10,000 and 1,000,000 Daltons. Larger molecular weights and longer molecular chains not only lead to higher viscosity characteristics of the finished resin, such as the viscosity range of medium-viscosity polyurethane is generally between 1000-10000mPa·s, but also affect the hardness and other performance of the resin, making it difficult to meet the needs of more application scenarios. Summary of the invention

[0007] In view of the above shortcomings, the purpose of the present invention is to provide a low-viscosity and high-hardness UV-curable polyurethane resin and a preparation method thereof, which can optimize the viscosity and hardness of the material; on the basis of having considerable insulation, it can ensure that it has low viscosity and high hardness, so as to meet the needs of preparing insulating ink. And it can greatly improve its comprehensive performance, so that it has excellent performance in viscosity, hardness, insulation, water boiling resistance, etc., and is suitable for the application scenario of power battery insulating ink printing process.

[0008] The technical solution adopted by the present invention is: a low-viscosity and high-hardness UV-curable polyurethane resin, comprising the following components in parts by weight:

[0009]

[0010] Furthermore, the hydroxy acrylate includes one or a combination of hydroxyethyl acrylate, hydroxypropyl acrylate, hydroxybutyl acrylate, and hydroxybutyl methacrylate.

[0011] The molecular formula of hydroxyethyl acrylate is C5H8O3, a colorless liquid. It is soluble in general organic solvents and miscible with water. Copolymers can be used as fiber treatment agents, thermosetting coatings, adhesives with high bonding strength, rubbers with both heat resistance and oil resistance (such as acrylic copolymer rubber), paper processing agents, lubricant additives, copolymers with acrylamide can be used as thickeners, copolymers with vinyl ether can be used as substitutes for floor wax, and copolymers with divinylbenzene can be used as ion exchange resins, etc. The molecular formula of hydroxypropyl acrylate is C6H10O3. It can be miscible with water in any proportion, and it also dissolves most organic solvents and is easy to polymerize. It can be used to produce adhesives, thermosetting coatings, fiber treatment agents and modifiers for synthetic resin copolymers, and can also be used to prepare lubricant additives, etc. As a functional monomer used as a cross-linking monomer for acrylic resin, it can improve the adhesion, weather resistance, drug resistance, impact resistance and gloss of the product. It is used to manufacture synthetic resins, adhesives, thermosetting coatings, etc. It is also used to make fiber treatment agents, latex, printing inks, medical materials, etc. The chemical formula of hydroxybutyl acrylate is C7H12O3. It has a high degree of freedom of hydroxyl groups and is highly reactive. It can be used to change the properties of various polymers. Highly cross-linked acrylates that can improve the low-temperature hardening, flexibility, scratch resistance and acid resistance of coatings and coating materials are used as raw materials for adhesives to improve bonding strength, correction and durability. It is most suitable as a raw material for polyurethane resins, etc.

[0012] Furthermore, the diisocyanate is one or a combination of diphenylmethane diisocyanate, isophorone diisocyanate and hexamethylene diisocyanate.

[0013] The chemical formula of diphenylmethane diisocyanate is C15H10N2O2. It is a colorless crystalline solid. It is in solid form at room temperature and is easily soluble in organic solvents such as methanol and ethanol. It is widely produced and used in industry. It is an important auxiliary agent, mainly used in the production of polyurethane plastics and elastomers. It can also be used in coatings, adhesives, sealants and other fields. Polyurethane prepolymers can be synthesized by reacting with polyols such as polyethers or polyesters. These polyurethane prepolymers can be further reacted with crosslinkers such as diols or diisocyanates. The chemical formula of isophorone diisocyanate is C12H18N2O2. It is an alicyclic diisocyanate and one of the basic raw materials for the manufacture of polyurethane. It can improve the light aging performance of the product and make the product have the advantage of non-yellowing color. It is also used to prepare polyurethane adhesives, etc. The polyurethane adhesive made of isophorone diisocyanate has excellent optical stability and chemical resistance. In two-component polyurethane coatings, it is used as an addition compound with triols to synthesize isocyanurate-type isocyanates, and is used in combination with alkyd resins, saturated polyesters, and hydroxy acrylic acid for large vehicle coatings and automotive repair coatings. The chemical formula of hexamethylene diisocyanate is C8H12N2O2. It is an important chemical raw material and is widely used in coatings, adhesives, elastomers, and plastics. It is often used as a cross-linking agent for polymers. By reacting with polyols to form a cross-linked structure, the hardness, wear resistance, and chemical resistance of the coating are improved. In addition, isocyanates can also copolymerize with other coating raw materials such as polyesters and epoxy resins to improve the performance and application range of the coating.

[0014] Furthermore, the catalyst is one or a combination of triethylenediamine, dimethyltin dineodecanoate, and dibutyltin dilaurate.

[0015] Furthermore, the polymerization inhibitor is one of p-methoxyphenol and p-tert-butylcatechol, or a complex of the two.

[0016] Furthermore, the diluent is one or a combination of methacrylate, ethoxyethoxyethyl acrylate and tetrahydrofuran acrylate.

[0017] Furthermore, the antioxidant is one of poly(dipropylene glycol) phenyl phosphite and 3,5-di-tert-butyl-4-hydroxyphenylpropionate isooctyl ester or a complex of the two.

[0018] Furthermore, the photoinitiator is one or a complex of phenylbis(2,4,6-trimethylbenzoyl)phosphine oxide and ethyl 2,4,6-trimethylbenzoylphenylphosphonate.

[0019] A method for preparing a low-viscosity and high-hardness ultraviolet light-cured polyurethane resin comprises the following steps:

[0020] After 30-45 parts by weight of hydroxy acrylate is charged into a reaction container, a mechanical stirrer is turned on and stirred at a speed of 250-300r / min. When the temperature is raised and maintained at 65-70°C, 0.1-0.2 parts of a catalyst and 1-3 parts of an inhibitor are added, the temperature is raised and maintained at 80-85°C, and after stirring evenly, 20-30 parts of a diisocyanate are added, wherein the diisocyanate should be divided into three equal parts and gradually added to the reaction container. After the addition is completed, the temperature is raised and maintained at 120-130°C. After reacting for 2 hours, 25-35 parts of a diluent and 1-3 parts of an antioxidant are added, after mixing evenly, the temperature is lowered to 40°C, and 1-5 parts of a photoinitiator are added. After stirring evenly, the material is discharged to obtain a low-viscosity and high-hardness UV-curable polyurethane resin.

[0021] The present invention has the following advantages: Compared with the traditional single-divided polyurethane, the present invention uses monohydric alcohol as a raw material, and the finished product is a polyurethane material with a small molecular weight and low viscosity. It has better leveling properties and is easy to process, extending the application scenarios of traditional polyurethane materials. In addition, because its cured product has high hardness, strong water resistance, moisture and heat resistance, and high insulation, it can be used as a surface insulating coating for transformers, batteries, chargers, and motor coils.

[0022] The present invention uses acrylic monomers and diisocyanate under the action of a catalyst to generate a polyester acrylate structure polymer containing amino ester. The polymer is a light-curing resin oligomer with a low molecular weight and cross-linking density, which improves the technical problems of traditional polyurethanes such as low hardness and high viscosity caused by high molecular weight and high cross-linking density.

[0023] The present invention adopts a one-pot synthesis method to synthesize the required photocurable resin, and the operation method is convenient, and the feeding method is simple, which is conducive to saving manpower input. After the reaction is completed, no subsequent purification treatment is required, and the product is directly stored as a finished product. When used, a photoinitiator and other additives required for the ink are added to make it a UV ink, which can achieve factory-scale large-scale production. The more prominent advantage is that unlike other photocurable resins that require reaction synthesis, no organic solvent is used in the reaction process of the present invention, which realizes the green and environmentally friendly nature of the product while greatly eliminating the safety hazards and risks caused by the use of organic solvents in factory-scale large-scale production.

[0024] The photocurable resin prepared by the present invention not only has good insulation performance through reasonable chemical reaction and formula design, but also has excellent performance in aging resistance and weather resistance. Currently, there are few brands and types of high-hardness, low-viscosity photocurable resins on the market, and it has broad application prospects in multiple fields such as electronic products, aviation, automobiles, and equipment manufacturing. With the continuous expansion of the scale of the industry, the convenience of product synthesis and the continuous improvement of the performance requirements of the finished product, the demand for low-viscosity and high-hardness UV-curable polyurethane resins will also expand and gain more favor.

[0025] On the other hand, compared with the patent CN201711064341.5 "A POSS-modified high-hardness polyurethane odor-free wood paint" which uses cage-type polysilsesquioxane-modified isocyanate trimer, the present invention has a smaller molecular weight, a lower viscosity of the finished product, better leveling, and is more conducive to atomization spraying in application, forming a uniform coating, and the product quality is more stable. In addition, the synthesis path of the patent CN201711064341.5 "A POSS-modified high-hardness polyurethane odor-free wood paint" is more complicated, requiring modification before synthesis, and there are more risks in large-scale production. Compared with the formula of high-functionality polyurethane and polyol used in patent CN202311480240.1 "A method for preparing a high-hardness, friction-resistant hardened coating", the formula of the present invention is less hydrophilic, which is conducive to long-term storage and ensures the long-term stability of the product. Because polyols are easily combined with water, if the water content increases, it will bring more obstacles to later applications. If there are ingredients that can react with water in the formula, it will destroy the overall state of the system.

[0026] In addition, the present invention has conducted a large number of hardness and viscosity tests, which can more accurately and obviously highlight the advantages of high leveling and high hardness of the product. The resin liquid samples prepared in all embodiments have excellent transparency and photocuring activity, and are suitable for application scenarios with certain requirements on color. The curing effect can be achieved in a shorter curing time. The resin surface is completely dry to the touch, smooth and glossy, which reduces energy loss and improves production efficiency to a certain extent. The resin cured samples prepared in all embodiments have high hardness and friction resistance before boiling and double 85 tests, which proves their excellent mechanical properties. In addition, their high insulation withstand voltage capability, transmittance of more than 90% and haze of less than 10% also indicate the excellent transparency of the resin material, proving that they can be used in optical equipment, electronic appliances and packaging materials. At the same time, after seven days of boiling in water, the basic properties of the cured samples prepared in most of the embodiments, such as hardness, friction resistance, transmittance and haze, can remain basically the same as those of the samples before boiling in water. After twenty-eight days of double 85 test, the basic properties of the cured samples prepared in all embodiments, such as hardness, friction resistance, transmittance and haze, can remain basically the same as those of the samples before boiling in water, indicating that the resin cured samples prepared in all embodiments have excellent boiling and moisture resistance, which solves the problems of high viscosity and low hardness of traditional polyurethane resins, and also improves the problems of cracking, bubbling, whitening and loss of gloss of light-cured resins after boiling in water and double 85 test, bringing more possibilities for the application of polyurethane resins.

[0027] The present invention will be further described below in conjunction with specific implementation modes. DETAILED DESCRIPTION

[0028] In order to more clearly understand the above-mentioned purpose, features and advantages of the present invention, the present invention is further described below in conjunction with embodiments. It should be noted that the embodiments of the present application and the features in the embodiments can be combined with each other without conflict.

[0029] Example 1

[0030] The present embodiment provides a method for preparing a low-viscosity and high-hardness UV-curable polyurethane resin, and a low-viscosity and high-hardness UV-curable polyurethane resin prepared by the method, and a low-viscosity and high-hardness UV-curable polyurethane resin prepared by the method.

[0031] Preparation of low viscosity and high hardness UV-curable polyurethane resin:

[0032] After 30 parts by weight of hydroxypropyl acrylate is charged into the reaction container, the mechanical stirrer is turned on and stirred at a speed of 250-300r / min. When the temperature is raised and maintained at 65-70°C, 0.1 parts of dibutyltin dilaurate and 4 parts of p-tert-butylcatechol are added, the temperature is raised and maintained at 80-85°C, and after stirring evenly, 20 parts of hexamethylene diisocyanate are added. The hexamethylene diisocyanate should be divided into three equal parts and gradually added to the reaction container. After the addition is completed, the temperature is raised and maintained at 120-130°C. After reacting for 2 hours, 40 parts of methacrylate and 3 parts of poly(dipropylene glycol) phenyl phosphite are added. After mixing evenly, the temperature is lowered to 40°C, and 3 parts of ethyl 2,4,6-trimethylbenzoylphenylphosphonate are added. After stirring evenly, the material is discharged to obtain a low-viscosity and high-hardness UV-curable polyurethane resin, which is named NS1.

[0033] Preparation of low viscosity and high hardness UV-curable polyurethane resin cured samples:

[0034] Take 10 parts of the prepared NS1 resin material, mix them evenly and spray them on the polished tinplate using UV spray equipment. The coating thickness is controlled at 110±2nm. After irradiation with a UV curing machine for 2-10s, a low-viscosity and high-hardness UV-curable polyurethane resin cured sample is obtained, which is named NS1-G.

[0035] Example 2

[0036] This embodiment provides a method for preparing a low-viscosity and high-hardness UV-curable polyurethane resin, and a low-viscosity and high-hardness UV-curable polyurethane resin prepared by the method.

[0037] Preparation of low viscosity and high hardness UV-curable polyurethane resin:

[0038] After 35 parts by weight of hydroxypropyl acrylate is charged into the reaction container, the mechanical stirrer is turned on and stirred at a speed of 250-300r / min. When the temperature is raised and maintained at 65-70°C, 0.1 parts of dibutyltin dilaurate and 4 parts of p-tert-butylcatechol are added, the temperature is raised and maintained at 80-85°C, and after stirring evenly, 22 parts of hexamethylene diisocyanate are added. The hexamethylene diisocyanate should be divided into three equal parts and gradually added to the reaction container. After the addition is completed, the temperature is raised and maintained at 120-130°C. After reacting for 2 hours, 33 parts of methacrylate and 3 parts of poly(dipropylene glycol) phenyl phosphite are added. After mixing evenly, the temperature is lowered to 40°C, and 3 parts of ethyl 2,4,6-trimethylbenzoylphenylphosphonate are added. After stirring evenly, the material is discharged to obtain a low-viscosity and high-hardness UV-curable polyurethane resin, which is named NS2.

[0039] Preparation of low viscosity and high hardness UV-curable polyurethane resin cured samples:

[0040] Take 10 parts of the prepared NS2 resin material, mix them evenly and spray them on the polished tinplate using UV spray equipment. The coating thickness is controlled at 110±2nm. After irradiation with a UV curing machine for 2-10s, a low-viscosity and high-hardness UV-curable polyurethane resin cured sample is obtained, which is named NS2-G.

[0041] Example 3

[0042] This embodiment provides a method for preparing a low-viscosity and high-hardness UV-curable polyurethane resin, and a low-viscosity and high-hardness UV-curable polyurethane resin prepared by the method.

[0043] Preparation of low viscosity and high hardness UV-curable polyurethane resin:

[0044] After 40 parts by weight of hydroxypropyl acrylate are charged into the reaction container, the mechanical stirrer is turned on and stirred at a speed of 250-300r / min. When the temperature is raised and maintained at 65-70°C, 0.1 parts of dibutyltin dilaurate and 4 parts of p-tert-butylcatechol are added, the temperature is raised and maintained at 80-85°C, and after stirring evenly, 25 parts of hexamethylene diisocyanate are added. The hexamethylene diisocyanate should be divided into three equal parts and gradually added to the reaction container. After the addition is completed, the temperature is raised and maintained at 120-130°C. After reacting for 2 hours, 25 parts of methacrylate and 3 parts of poly(dipropylene glycol) phenyl phosphite are added. After mixing evenly, the temperature is lowered to 40°C, and 3 parts of ethyl 2,4,6-trimethylbenzoylphenylphosphonate are added. After stirring evenly, the material is discharged to obtain a low-viscosity and high-hardness UV-curable polyurethane resin, which is named NS3.

[0045] Preparation of low viscosity and high hardness UV-curable polyurethane resin cured samples:

[0046] Take 10 parts of the prepared NS3 resin material, mix them evenly and spray them on the polished tinplate using UV spray equipment. The coating thickness is controlled at 110±2nm. After irradiation with a UV curing machine for 2-10s, a low-viscosity and high-hardness UV-curable polyurethane resin cured sample is obtained, which is named NS3-G.

[0047] Example 4

[0048] This embodiment provides a method for preparing a low-viscosity and high-hardness UV-curable polyurethane resin, and a low-viscosity and high-hardness UV-curable polyurethane resin prepared by the method.

[0049] Preparation of low viscosity and high hardness UV-curable polyurethane resin:

[0050] After 35 parts by weight of hydroxypropyl acrylate is charged into the reaction container, the mechanical stirrer is turned on and stirred at a speed of 250-300r / min. When the temperature rises and is maintained at 65-70°C, 0.1 parts of dibutyltin dilaurate and 4 parts of p-tert-butylcatechol are added, the temperature is raised and maintained at 80-85°C, and after stirring evenly, 22 parts of hexamethylene diisocyanate are added. The hexamethylene diisocyanate should be divided into three equal parts and gradually added to the reaction container. After the addition is completed, The temperature was raised and maintained at 120-130°C. After reacting for 2 hours, 33 parts of methyl methacrylate and 3 parts of poly(dipropylene glycol) phenyl phosphite were added and mixed evenly. The temperature was then lowered to 40°C, and 1.5 parts of ethyl 2,4,6-trimethylbenzoylphenylphosphonate and 1.5 parts of phenylbis(2,4,6-trimethylbenzoyl)phosphine oxide were added. After stirring evenly, the material was discharged to obtain a low-viscosity and high-hardness UV-curable polyurethane resin, which was named NS4.

[0051] Preparation of low viscosity and high hardness UV-curable polyurethane resin cured samples:

[0052] Take 10 parts of the prepared NS4 resin material, mix them evenly and spray them on the polished tinplate using UV spray equipment. The coating thickness is controlled at 110±2nm. After irradiation with a UV curing machine for 2-10s, a low-viscosity and high-hardness UV-curable polyurethane resin cured sample is obtained, which is named NS4-G.

[0053] Example 5

[0054] This embodiment provides a method for preparing a low-viscosity and high-hardness UV-curable polyurethane resin, and a low-viscosity and high-hardness UV-curable polyurethane resin prepared by the method.

[0055] Preparation of low viscosity and high hardness UV-curable polyurethane resin:

[0056] After 35 parts by weight of hydroxypropyl acrylate is loaded into the reaction container, the mechanical stirrer is turned on and stirred at a speed of 250-300r / min. When the temperature rises and is maintained at 65-70°C, 0.1 parts of dibutyltin dilaurate and 4 parts of p-tert-butylcatechol are added, the temperature is raised and maintained at 80-85°C, and after stirring evenly, 22 parts of hexamethylene diisocyanate are added. The hexamethylene diisocyanate should be divided into three equal parts and gradually added to the reaction container. When the addition is completed, Then, the temperature is raised and maintained at 120-130°C. After reacting for 2 hours, 32 parts of methyl methacrylate and 3 parts of poly(dipropylene glycol) phenyl phosphite are added and mixed evenly. The temperature is then lowered to 40°C, and 2 parts of ethyl 2,4,6-trimethylbenzoylphenylphosphonate and 2 parts of phenylbis(2,4,6-trimethylbenzoyl)phosphine oxide are added. After stirring evenly, the material is discharged to obtain a low-viscosity and high-hardness UV-curable polyurethane resin, which is named NS5.

[0057] Preparation of low viscosity and high hardness UV-curable polyurethane resin cured samples:

[0058] Take 10 parts of the prepared NS5 resin material, mix them evenly and spray them on the polished tinplate using UV spray equipment. The coating thickness is controlled at 110±2nm. After irradiation with a UV curing machine for 2-10s, a low-viscosity and high-hardness UV-curable polyurethane resin cured sample is obtained, which is named NS5-G.

[0059] Example 6

[0060] This embodiment provides a method for preparing a low-viscosity and high-hardness UV-curable polyurethane resin, and a low-viscosity and high-hardness UV-curable polyurethane resin prepared by the method.

[0061] Preparation of low viscosity and high hardness UV-curable polyurethane resin:

[0062] After 35 parts by weight of hydroxyethyl acrylate is loaded into the reaction container, the mechanical stirrer is turned on and stirred at a speed of 250-300r / min. When the temperature rises and is maintained at 65-70°C, 0.1 parts of dibutyltin dilaurate and 4 parts of p-tert-butylcatechol are added, the temperature is raised and maintained at 80-85°C, and after stirring evenly, 22 parts of hexamethylene diisocyanate are added. The hexamethylene diisocyanate should be divided into three equal parts and gradually added to the reaction container. After the addition is completed, the temperature is raised and maintained at 120-130°C. After reacting for 2 hours, 32 parts of methyl methacrylate and 3 parts of poly(dipropylene glycol) phenyl phosphite are added. After mixing evenly, the temperature is lowered to 40°C, and 2 parts of ethyl 2,4,6-trimethylbenzoylphenylphosphonate and 2 parts of phenylbis(2,4,6-trimethylbenzoyl)phosphine oxide are added. After stirring evenly, the material is discharged to obtain a low-viscosity and high-hardness UV-curable polyurethane resin.

[0063] Preparation of low viscosity and high hardness UV-curable polyurethane resin cured samples:

[0064] Take 10 parts of the prepared NS6 resin material, mix them evenly and spray them on the polished tinplate using UV spray equipment. The coating thickness is controlled at 110±2nm. After irradiation with a UV curing machine for 2-10s, a low-viscosity and high-hardness UV-curable polyurethane resin cured sample is obtained, which is named NS6-G.

[0065] Example 7

[0066] This embodiment provides a method for preparing a low-viscosity and high-hardness UV-curable polyurethane resin, and a low-viscosity and high-hardness UV-curable polyurethane resin prepared by the method.

[0067] Preparation of low viscosity and high hardness UV-curable polyurethane resin:

[0068] After 35 parts by weight of hydroxybutyl methacrylate is charged into the reaction container, the mechanical stirrer is turned on and stirred at a speed of 250-300r / min. When the temperature rises and is maintained at 65-70°C, 0.1 parts of dibutyltin dilaurate and 4 parts of p-tert-butylcatechol are added, the temperature is raised and maintained at 80-85°C, and after stirring evenly, 22 parts of hexamethylene diisocyanate are added. The hexamethylene diisocyanate should be divided into three equal parts and gradually added to the reaction container. After the addition is completed, After the reaction is completed, the temperature is raised and maintained at 120-130°C. After reacting for 2 hours, 32 parts of methyl methacrylate and 3 parts of poly(dipropylene glycol) phenyl phosphite are added. After mixing evenly, the temperature is lowered to 40°C, and 2 parts of ethyl 2,4,6-trimethylbenzoylphenylphosphonate and 2 parts of phenylbis(2,4,6-trimethylbenzoyl)phosphine oxide are added. After stirring evenly, the material is discharged to obtain a low-viscosity and high-hardness UV-curable polyurethane resin, which is named NS7.

[0069] Preparation of low viscosity and high hardness UV-curable polyurethane resin cured samples:

[0070] Take 10 parts of the prepared NS7 resin material, mix them evenly and spray them on the polished tinplate using UV spray equipment. The coating thickness is controlled at 110±2nm. After irradiation with a UV curing machine for 2-10s, a low-viscosity and high-hardness UV-curable polyurethane resin cured sample is obtained, which is named NS7-G.

[0071] The above embodiments are tested as follows, and the test results are comprehensively compared and analyzed.

[0072] The resin obtained in each example was subjected to visual inspection, viscosity, and LED curing surface dryness test. The results are shown in Table 1.

[0073] Among them, viscosity test: the low viscosity and high hardness UV-curable polyurethane resin obtained in each embodiment is tested using a rotational viscometer, using rotor No. 1 and a test temperature of 25°C, so as to determine the viscosity (cps) of the low viscosity and high hardness UV-curable polyurethane resin. LED curing surface dry test: 230ul of the low viscosity and high hardness UV-curable polyurethane resin obtained in each embodiment is taken and sprayed on a 25cm*4cm tinplate after grinding using a UV spraying device. The coating thickness is controlled at 110±2 nm, and a 395nm LED is used for curing (3000mj / cm2). The surface curing degree is evaluated and the curing time is recorded. The test result of complete dryness to touch is pass, and the surface stickiness is NG.

[0074] Table 1:

[0075] sample Appearance (visual inspection) Viscosity(cps) Curing time(s) Dry state NS1 Clarity and transparency 40 3.8 pass NS2 Clarity and transparency 37 4.5 pass NS3 Clarity and transparency 33 4.9 pass NS4 Clarity and transparency 36 2.9 pass NS5 Clarity and transparency 37 2.5 pass NS6 Clarity and transparency 42 3.5 pass NS7 Clarity and transparency 48 4.8 pass

[0076] The resin cured samples obtained in each embodiment were subjected to mechanical property tests before boiling, seven days of boiling and twenty-eight days of double 85. To ensure the simplicity of the test results, the sample NS 1-G after seven days of boiling was marked as NS 1-G-7, the sample NS 1-G after twenty-eight days of double 85 testing was marked as NS 1-G-28, and the other samples were similarly tested. The results are shown in Table 2.

[0077] Among them, the hardness test is carried out in accordance with GB / T 6739-2006 "Determination of film hardness by pencil method for paint and varnish", and the test is repeated three times to take the average value. Friction resistance test: The test is carried out using a steel wool friction tester, applying a pressure of 1000g and a speed of 50 times / minute. The transmittance and haze tests are tested in accordance with ASTM D1003-13 "Standard Test Method for Transmittance and Haze of Transparent Plastic Materials". Insulation withstand voltage test: Each embodiment is tested with a GPT-9803 voltage / insulation resistance tester, and the test conditions are DC 6000V, 60s, AC 5000V, 60s; read the test results, if the leakage current is less than 1mA, the result is pass, if the leakage current is greater than 1 mA, the result is NG. The results are shown in Table 2.

[0078] Table 2:

[0079]

[0080]

[0081] It can be seen from the results in Table 1 that the resin liquid samples prepared in all embodiments have excellent transparency and photocuring activity, and are suitable for application scenarios with certain requirements for color. A shorter curing time can achieve the curing effect, and the resin surface is completely dry to the touch, smooth, and glossy. While reducing energy loss, it also improves production efficiency to a certain extent. In addition, it can be seen that in Examples 1-3, the difference is that from the test results, it can be seen that with the reduction of the amount of hydroxy acrylate and isocyanate added, and the increase in the amount of diluent added, the viscosity of the resin system gradually decreases, indicating that the diluent has a good dilution effect and viscosity improvement effect, and the curing time of Examples 1-3 shows a trend of gradual increase, indicating that the introduced diluent does not increase the curing time to a certain extent. Considering the two aspects of curing rate and the need for the resin to have a suitable viscosity for subsequent curing spraying, Example 2 is preferred.

[0082] Example 4 is based on Example 2, while keeping the total amount of photoinitiator fixed, another photoinitiator is added, and Example 5 is based on Example 4, the total amount of photoinitiator is also increased from 3% to 4%. The test results show that the curing time of the photocurable resin is reduced from 4.5s in Example 2 to 3.9s in Example 4, and the curing time of Example 5 is reduced to 3.3s, indicating that appropriately increasing the content of photoinitiator and increasing the type of photoinitiator can effectively improve the curing rate and degree, so Example 5 is preferred, that is, the amount of photoinitiator is 4%, respectively 2% of 2,4,6-trimethylbenzoylphenylphosphonic acid ethyl ester and 2% of phenylbis(2,4,6-trimethylbenzoyl)phosphine oxide. Furthermore, Examples 6-7 are based on Example 5, only the type of hydroxy acrylate is changed, Example 6 is hydroxyethyl acrylate, and Example 7 is hydroxybutyl acrylate. The results show that the resin synthesized by hydroxyethyl acrylate has lower viscosity, shorter curing time and higher hardness. The reason is that hydroxypropyl acrylate has the smallest molecular weight and the lowest viscosity. Similarly, at the same mass fraction, the double bond active group density of hydroxypropyl acrylate is higher than that of hydroxypropyl acrylate and hydroxybutyl acrylate.

[0083] From the results in Table 2, it can be seen that the resin cured samples prepared in all embodiments have high hardness and friction resistance before boiling and double 85 test, which proves their excellent mechanical properties. In addition, its high insulation withstand voltage capability, transmittance of more than 90% and haze of less than 10% also show the excellent transparency of the resin material, proving that it can be used in optical equipment, electronic appliances and packaging materials. At the same time, after boiling for seven days, the basic properties of the hardness, friction resistance, transmittance and haze of the cured samples prepared in most embodiments can be kept basically the same as those before boiling. After the double 85 test for twenty-eight days, the basic properties of the hardness, friction resistance, transmittance and haze of the cured samples prepared in all embodiments can be kept basically the same as those before boiling, indicating that the resin cured samples prepared in all embodiments have excellent boiling resistance and moisture and heat resistance, solving the problems of high viscosity and low hardness of traditional polyurethane resin, and improving the problems of cracking, bubbling, whitening and loss of gloss of light-cured resin after boiling and double 85 test, bringing more possibilities for the application of polyurethane resin.

[0084] The present invention is not limited to the above-mentioned embodiments. Other low-viscosity and high-hardness UV-curable polyurethane resins and preparation methods thereof obtained by using the same or similar technical features as the above-mentioned embodiments of the present invention are within the protection scope of the present invention.

Claims

1. A low-viscosity and high-hardness UV-curable polyurethane resin, characterized in that: The composition comprises the following components in parts by weight:

2. The low-viscosity and high-hardness UV-curable polyurethane resin according to claim 1, characterized in that: The hydroxy acrylate includes one or a combination of hydroxyethyl acrylate, hydroxypropyl acrylate, hydroxybutyl acrylate and hydroxybutyl methacrylate.

3. The low-viscosity and high-hardness UV-curable polyurethane resin according to claim 1, characterized in that: The diisocyanate is one or a combination of diphenylmethane diisocyanate, isophorone diisocyanate and hexamethylene diisocyanate.

4. The low-viscosity and high-hardness UV-curable polyurethane resin according to claim 1, characterized in that: The catalyst is one or a combination of triethylenediamine, dimethyltin dineodecanoate and dibutyltin dilaurate.

5. The low-viscosity and high-hardness UV-curable polyurethane resin according to claim 1, characterized in that: The polymerization inhibitor is one of p-methoxyphenol and p-tert-butylcatechol or a composite of the two.

6. The low-viscosity and high-hardness UV-curable polyurethane resin according to claim 1, characterized in that: The diluent is one or a combination of methacrylate, ethoxyethoxyethyl acrylate and tetrahydrofuran acrylate.

7. The low-viscosity and high-hardness UV-curable polyurethane resin according to claim 1, characterized in that: The antioxidant is one of poly(dipropylene glycol) phenyl phosphite and 3,5-di-tert-butyl-4-hydroxyphenylpropionate isooctyl ester or a composite of the two.

8. The low-viscosity and high-hardness UV-curable polyurethane resin according to claim 1, characterized in that: The photoinitiator is one of phenylbis(2,4,6-trimethylbenzoyl)phosphine oxide and ethyl 2,4,6-trimethylbenzoylphenylphosphonate or a composite of the two.

9. A method for preparing the low-viscosity and high-hardness UV-curable polyurethane resin according to any one of claims 1 to 8, characterized in that: The steps include: After 30-45 parts by weight of hydroxy acrylate is charged into a reaction container, a mechanical stirrer is turned on and stirred at a speed of 250-300r / min. When the temperature is raised and maintained at 65-70°C, 0.1-0.2 parts of a catalyst and 1-3 parts of an inhibitor are added, the temperature is raised and maintained at 80-85°C, and after stirring evenly, 20-30 parts of a diisocyanate are added, wherein the diisocyanate should be divided into three equal parts and gradually added to the reaction container. After the addition is completed, the temperature is raised and maintained at 120-130°C. After reacting for 2 hours, 25-35 parts of a diluent and 1-3 parts of an antioxidant are added, after mixing evenly, the temperature is lowered to 40°C, and 1-5 parts of a photoinitiator are added. After stirring evenly, the material is discharged to obtain a low-viscosity and high-hardness UV-curable polyurethane resin.

Citation Information

Patent Citations

  • A POSS-modified high-hardness polyurethane odor-free wood coating

    CN107936814B

  • Preparation method of high-hardness friction-resistant hardened coating

    CN117511385A